Dietary Valine Requirement of Juvenile Olive Flounder (Paralichthys olivaceus) - Jaehyeong Shin; Deahyun Ko; Mirasha Hasanthi; Gunho Eom; Kyeong–Jun Lee (Aquaculture Nutrition)
This study was conducted to estimate dietary valine (Val) requirement for juvenile olive flounder (Paralichthys olivaceus). In a feeding trial, a total of 540 fish (initial body weight: 23.0 ± 0.2 g) were stocked into 18 tanks (210 L). Six experimental diets containing graded levels of Val (4, 8, 12, 16, 20, and 24 g/kg, dry matter basis) were fed to the fish in triplicate groups for 13 weeks. The lowest growth, feed utilization, and survival were observed in 4 g/kg Val group (P<0.05). Dietary Val deficiency resulted in significant decreases (P<0.05) in whole-body protein and Val concentrations, hepatosomatic index, condition factor and plasma protein and cholesterol levels. Nonspecific immunity and antioxidant activities were significantly lower (P<0.05) in 4 g/kg Val group than in other groups. Dietary Val deficiency upregulated the expression of proinflammatory cytokines and downregulated the expression of anti-inflammatory cytokines and intestinal tight junction protein (occludin) (P<0.05). Mucosal fold height and submucosa and muscularis thickness of fish intestine were significantly lower (P<0.05) in fish fed 4 g/kg Val diet. Relatively lower lipid droplet in hepatic cell was observed in 4 g/kg Val group. Our findings suggested that dietary Val requirements for juvenile olive flounder would be 17.7–18.9 g Val/kg (35.4–37.8 g/kg on the basis of crude protein), estimated by quadratic regression analysis based on the weight gain, protein efficiency ratio, and protein retention efficiency.